Understanding global poverty : causes, solutions, and capabilities - Cosgrove, Serena, 1963-; Curtis, Benjamin W., 1972- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Understanding Global Poverty introduces students to the study and analysis of poverty, helping them to understand why it is pervasive across human societies, and how it can be reduced through proven policy solutions. The book uses the capabilities and human development approach to foreground the human aspects of poverty, keeping the voices, experiences and needs of the world's poor central to the analysis. Starting with definitions and measurement, the book goes on to explore the causes of poverty and how poverty reduction programs and policy have responded in practice. The book also reflects on the ethics of why we should work to reduce poverty and what actions readers themselves can take. This new edition has been revised and updated throughout, featuring: a new chapter on migration and refugees additional international examples, including material on Mexico, Covid-19 in global perspective, and South-South development initiatives information on careers in international development; insights into how various forms of social difference, including race, ethnicity, social class, gender, and sexuality relate to poverty. Fully interdisciplinary in approach, the book is also supplemented with case studies, discussion questions and further reading suggestions in order to support learning. Perfect as an introductory textbook for students across sociology, global development, political science, anthropology, public health and economics, Understanding Global Poverty will also be a valuable resource to policy makers and development practitioners"--
List of maps -- List of contributors -- Acknowledgements -- Preface -- Building a framework for understanding poverty -- Development and its debates -- Multidimensional measurements of poverty and wellbeing -- Health and poverty -- Geographical and spatial poverty -- Race, class, gender, and poverty -- State institutions, governance, and poverty -- Conflict and poverty -- Migration and poverty reduction -- Education as poverty reduction -- The environment and poverty reduction -- Financial services for the poor -- Conclusion : ethics and action : what should you do about global poverty? -- Appendix : careers in international development.
OCLC-licensed vendor bibliographic record.
Keywords: Poverty; Economic development; POLITICAL SCIENCE / Economic Conditions; SOCIAL SCIENCE / Third World Development; SOCIAL SCIENCE / Poverty